2008
DOI: 10.1111/j.1365-4632.2008.03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Chanarin–Dorfman syndrome with eccrine gland vacuolation: a case report

Abstract: Chanarin-Dorfman syndrome is a rare congenital disorder of lipid metabolism characterized by ichthyosis, leukocytic vacuolation (Jordan's anomaly), and variable involvement of the liver and neuromuscular system, with about 40 cases described worldwide to date. We report one more case of this rare syndrome, with certain peculiarities, namely vacuolation in eccrine glands, in a young male adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Emollients are useful for local treatment [13]. Kakourou et al [14] prescribed a low-fat diet to their CDS patient and observed improvement in skin and liver manifestations during 1 year of the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Emollients are useful for local treatment [13]. Kakourou et al [14] prescribed a low-fat diet to their CDS patient and observed improvement in skin and liver manifestations during 1 year of the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuolization has also been shown in other cells such as myocytes, hepatocytes, fibroblasts and keratinocytes. To our knowledge, only two previously reported cases were described to show vacuolization of the eccrine glands such as seen in our patient, and may be the cause of the hypohidrosis seen in such patients.…”
mentioning
confidence: 46%
“…Other clinical findings aside from ichthyosis include hepatomegaly, bilateral ectropion, cataract, muscle weakness, bilateral sensorineural deafness, splenomegaly, short stature, small ears, strabismus and mental retardation 64–74 . In addition, clinical findings, such as microcephaly, cardiomyopathy, nystagmus, eclabion, rickets, renal eccrine gland and pancreatic involvement, are also observed in rare cases 75–80 . The most common clinical findings in patients were ichtyosis 100% and hepatomegaly 60%, and the others were bilateral ectropion, cataract, neurosensory deafness and splenomegaly (29%, 22%, 17% and 13% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66][67][68][69][70][71][72][73][74] In addition, clinical findings, such as microcephaly, cardiomyopathy, nystagmus, eclabion, rickets, renal eccrine gland and pancreatic involvement, are also observed in rare cases. [75][76][77][78][79][80] The most common clinical findings in patients were ichtyosis 100% and hepatomegaly 60%, and the others were bilateral ectropion, cataract, neurosensory deafness and splenomegaly (29%, 22%, 17% and 13% respectively).…”
Section: Liver Disease Liver Phenotype Genotype/mutationmentioning
confidence: 99%